Microalgal pandora for potent bioenergy production: A way forward?. (1st February 2023) - Banerjee, Srijoni; Ghosh, Dipankar; Pandit, Chetan; Saha, Sagnik; Mohapatra, Anwesha; Pandit, Soumya; Sharma, Minaxi; Sridhar, Kandi; Stephen Inbaraj, Baskaran; Prasad, Ram
Graphical abstract: Highlights: Microalgae (MA) as biomass source for generation of biofuel, bioenergy & bioeconomy. Biohydrogen production from MA, wastewater treatment & limitations are summarized. Biomethane from MA, anaerobic digestion & biogas-biomethane conversion are discussed. Bioelectricity production from MA with principle and limitations are illustrated. Bioethanol production from MA and life cycle assessment of MA biofuel are elucidated. Abstract: Microalgae have shown their extravagant potency as a prominent source for the production of biomass, which has opened the gates for biofuel, bioenergy generation, and down-streaming in today's third-world developing countries. They are competent in producing smaller land footprints while engendering high yields of biomass and fuel overall. By their nature, they have the potential to avail the land that is incapacitated for food production and flourishes there without bringing forth disruption to the economy in any form. Since microalgae are perennial along with excellent tolerance towards pH changes, their current demand is skyrocketing. The review paper, sails on the generation of biohydrogen, biomethane, and bioelectricity using microalgae as the primordial constituents, with the mechanisms and pitfalls confronted throughout the process. Alongside, this paper also covers the involvement of microalgae in the treatment of wastewater and biohydrogen production using dark fermentation. Biomethane is one of the prime biogas generated upon methanogenesis and fermentation when carried out employing microalgae. The paper's greater aims are also to highlight the production of bioelectricity using microbial electrochemical cells and microbial fuel cells. The outcome of this review can provide a research update on the efficiency of algal biomass as a promising raw material for various biofuels paving a way for finding research gaps towards future exploration.